Vps34-mediated macropinocytosis in Tuberous Sclerosis Complex 2-deficient cells supports tumorigenesis - Harilaos Filippakis (Nature Portfolio, 2018)
Abstract Tuberous Sclerosis Complex (TSC), a rare genetic disorder with mechanistic target of rapamycin complex 1 (mTORC1) hyperactivation, is characterized by multi-organ hamartomatous benign tumors including brain, skin, kidney, and lung (Lymphangioleiomyomatosis). mTORC1 hyperactivation drives metabolic reprogramming including glucose and glutamine utilization, protein, nucleic acid and lipid synthesis. To investigate the mechanisms of exogenous nutrients uptake in Tsc2-deficient cells, we measured dextran uptake, a polysaccharide internalized via macropinocytosis. Tsc2-deficient cells showed a striking increase in dextran uptake (3-fold, p < 0.0001) relative to Tsc2-expressing cells, which was decreased (3-fold, p < 0.0001) with mTOR inhibitor, Torin1. Pharmacologic and genetic inhibition of the lipid kinase Vps34 markedly abrogated uptake of Dextran in Tsc2-deficient cells. Macropinocytosis was further increased in Tsc2-deficient cells that lack autophagic mechanisms, suggesting that autophagy inhibition leads to dependence on exogenous nutrient uptake in Tsc2-deficient cells. Treatment with a macropinocytosis inhibitor, ethylisopropylamiloride (EIPA), resulted in selective growth inhibition of Atg5-deficient, Tsc2-deficient cells (50%, p < 0.0001). Genetic inhibition of autophagy (Atg5−/− MEFs) sensitized cells with Tsc2 downregulation to the Vps34 inhibitor, SAR405, resulting in growth inhibition (75%, p < 0.0001). Finally, genetic downregulation of Vps34 inhibited tumor growth and increased tumor latency in an in vivo xenograft model of TSC. Our findings show that macropinocytosis is upregulated with Tsc2-deficiency via a Vps34-dependent mechanism to support their anabolic state. The dependence of Tsc2-deficient cells on exogenous nutrients may provide novel approaches for the treatment of TSC.